ANALYSIS OF ECOLOGICAL PROPERTIES OF TRADITIONAL AND ALTERNATIVE AVIATION GAS COMPONENTS - Бойченко, Сергій Валерійович; Павлюх, Леся Іванівна; Шкільнюк, Ірина Олександрівна; Яковлєва, Анна Валеріївна; Матвєєва, Ірина Валеріївна; Гудзь, Аліна Валеріївна (Science-based technologies, 2019)
The work is devoted to the analysis of environmental properties of aviation gasolines and substantiation of its optimal component composition for providing sufficient exploitation and environmental performance. During the study the technogenic impact of processes of oil extraction and processing was considered. The processes of oil refining and aviation gasolines production were analyzed. Environmental properties of conventional and alternative aviation gasolines were analyzed in the presented article. The influence of individual hydrocarbon components, found in gasolines, on its environmental properties as well as level of toxicity of hydrocarbon components was shown. It was found that decreasing of aromatic hydrocarbons content in gasolines with simultaneous application of oxygenate, can improve the composition of aviation gasolines. It can help to reduce formation of carbon monoxide and unburned hydrocarbons emissions during combustion. Increasing of octane number causes reduction of toxic gases concentration in emissions; thus environmental properties of aviation gasolines are improved. Later the comparative characteristics of physical-chemical properties of conventional aviation and motor gasolines, some oxygenates, such as methanol, ethanol and buthanol, and hydrogen was developed and analyzed. It was found that adding oxygenates, mainly ethanol, into the composition of alternative aviation gasoline helps improving its octane number, thus it will have positive effect on exploitation of aviation internal combustion engines, as well as improving exhaust gases composition in a result of gasolines combustion. It was proposed the optimal content of ethanol oxygenate in the composition of aviation gasoline – 25 %. In a result of the work it was concluded that using of oxygenates improves environmental properties of alternative aviation gasolines. This may contribute to improving of exploitation properties of aviation gasolines and also minimization of aviation industry impact on environment.